Filial piety in confucianism and Islam: a comparative literary analysis of Quran, Hadith and four Chinese classics - Muhamad Shukri, Abdul Salam; Abdullah @ Chuah Hock Leng, Osman; Othman, Normala (Pluto Journals, 2011)
This article is an attempt to compare the teachings of Confucius and Islam, speciﬁcally The Four Books, which are authoritative works on Confucius, and the original sources of Islam, Qur’ān and Sunnah. The Four Books are the most quoted sources of Confucius’ thought, namely The Great Learning (Da Xue 大学), The Doctrine of the Mean (Zhong Yong 中庸), The Confucian Analects (Lun Yu 论) and The Works of Mencius (Mengzi 孟子). The focus shall be on the concept of family and ﬁlial piety as found in Confucianism and Qur’ān and Sunnah. Both the teachings of Confucius and Islam emphasise the importance of virtues, ties and order in the family system, for example, the husband is the head of the family and responsible for the family’s existence and security. Islam and Confucianism are both patriarchal, and the husband and men are protectors of the family and deserve much respect. Young members of the family must respect and obey the elders and vice versa. To Confucius, these virtues are the heavenly way and must be cultivated and developed accordingly as li (礼) or good manners from an early age. The young and old must be treated according to their age. Similar values are also upheld in Islam. However, there are also differences between the two approaches which shall be highlighted as well.